ANALISIS IMPLEMENTASI PRINSIP KEADILAN DALAM PROSES PENYELESAIAN KEBERATAN PAJAK PADA DIREKTORAT JENDERAL PAJAK - Devi Purnama Sari (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2016)
This research is performed to analyze if Tax Objection process has fulfilled the equity principle, to find obstacles in fulfilling the equity principle in the Objection process and also to find the ideal model of Tax Objection Process so that equity principle can obtained by the tax payers. The research is performed using qualitative method through observation, documentation study and interviewing 10 experienced informants in taxation. According to the research known that the equity principle has not been fulfilled in the Objection process, these happens because of some obstacles for instance the psychological matter met by the tax authority whom have to fulfill revenue target from tax payers, lack of understanding from both Tax payers and fiscus regarding tax regulations, the DGT internal policy to “Decline” any of Tax Objection request from Tax payers and also traumatic problem of fiscus for having GT-like case and/or criminalization case of tax authority by the DGT. Finally, the ideal model proposal concerning Tax Objection Institution is to shifted from DGT to be directly under the Ministry of Finance or upgraded the institution to be a pure court in the environment of justice power by establishing Tax Court Level I and the existing Tax Court to be a Higher Tax Court.